Rapid Late Quaternary Slip, Repeated Prehistoric Earthquake Rupture, and Widespread Landsliding Associated With the Karakudzhur Thrust, Central Kyrgyz Tien Shan. Issue 11 (31st October 2019) - Campbell, G. E.; Walker, R. T.; Abdrakhmatov, K.; Carolin, S.; Carr, A. S.; Elliott, J. R.; Jackson, J.; Mackenzie, D.; Rizza, M.; Rodes, A.
Abstract: Field studies have shown that active faulting in the SW Tien Shan is distributed across a series of E‐W reverse faults along the range fronts and within basin interiors, with summed shortening rates that are consistent with GPS measurements. In contrast, few field studies have been undertaken to determine the distribution, and the average slip rates, of faults in the central and eastern parts of the Tien Shan. In this paper we use remote and field‐based observations to characterize the active faulting and tectonic geomorphology of the Karakudzhur Basin in the central Tien Shan of Kyrgyzstan. We use radiocarbon, luminescence, and uranium series dating to provide ages on three fluvial terraces that are vertically displaced across the basin‐bounding reverse fault and estimate fault slip rates using a 20°S dipping fault exposure. We find that the fault has a slip‐rate of ∼2.4–5.9 mm/year averaged over the Holocene, indicating that it accommodates a major part of the shortening measured by GPS. In contrast to the relatively uniform distribution of N‐S shortening in the SW Tien Shan, significant shortening may instead be concentrated at present on a few active faults in the northern part of the central Tien Shan. The fresh geomorphic expression of the Karakudzhur fault suggests that it has ruptured in recent prehistory in a large‐magnitude M w ≥ 7 earthquake. From palaeoseismic trenching we show that two significant surface rupturing earthquakes have occurred since 2.4 ka. The most recent earthquake was potentially accompanied by widespread landsliding and faulting in the surrounding highlands. Key Points: Identification of rapid slip on a thrust fault in the central Tien Shan of Kyrgyzstan Repeated surface rupturing earthquakes in the last few thousand years Shows that significant shortening occurs within high‐elevation basins in range interior